Loafing behind screens: Of websites and work-avoidance - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
While most people will agree that the internet has given rise to greater efficiency and productivity, there are concerns that these technologies increasingly represent a threat to the workplace – as an instrument for distraction and loafing around. What might influence people to submit to the temptations of news, entertainment and social networking sites, and to avoid work? SMU assistant professor David T. Wagner studied internet traffic patterns to find out more.